Efektivitas Model Pembelajaran Inkuiri Terbimbing dalam Pembelajaran IPA di Sekolah Dasar - Tiva Mulia; Ari Suriani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Through literature analysis, this study aims to evaluate the effectiveness of the guided inquiry learning paradigm in teaching science at the primary school level. The methodology used in this research is qualitative, characterized by a literature review that analyzes various publications related to the implementation of the guided inquiry model. The results of the analysis show that the inquiry learning approach is effective for increasing student learning achievement, improving science processes, and increasing student learning motivation in science subjects. This model facilitates students to be actively involved in the learning process while still receiving direction from the teacher. The results of this study indicate that a directed inquiry learning model can serve as an effective alternative for science learning in primary schools.